Design of hand-Sized Torpedo-Like Fish Robot with the Dynamics and Hydrodynamics Analysis - Naser, Farah Abbas (Journal of Applied Nonlinear Dynamics, 2026)
Robotic fish have evolved to accomplish numerous inaccessible tasks and investigations in unreachable aquatic environments. Recently, the increasing interest in underwater exploration motivates the development of aquatic unmanned vehicles. Biomimetic robots have been developed by researchers based on the different parameters including maneuverability, cruising speed, and propulsion efficiency. This paper presents a design of torpedo-like fish robot with the required dynamics and hydrodynamics performance characteristics through Computational Fluid Dynamic application (SolidWorks Flow Simulation). The suggested model is built with a torpedo-shape to reduce drag forces while increasing thrust. The robot is propelled by a propeller fan with different number of blades (i.e., 2, 3, 4 and 5 blades). The propeller is actuated by a dc motor with (0 to 100 RPM). The required dynamics like motor torque, power consumption and angular velocities were calculated and compared with the hand calculations to validate our design.